Windows integrated development environment graphical user interface for MC-11 DATS - Ahmad Firdaus Ahmad Fadzil (2023)
The purpose of this thesis is to research and implement an alternative method in using microcontroller development boards, specifically M68HC11 based development boards such as EVBU and MC11-DATS. The proposed system is a windows based software that serves as a control centre when developing MC68BC11 applications using MC11-DATS and AS11, a MS-DOS based MC68HC11 cross assembler. This software is to be called WIDEGUI11, an acronym for 'Windows Integrated Development Environment Graphical User Interface for MC11-DATS.